Wakafpreneur as an Instrument of Islamic Da'wah and Social Transformation in the Philanthropic Institution - Zainur, Zainur; Yafiz, Muhammad; Nasution, Yenni Samri Juliati (MUHARRIK: Jurnal Dakwah dan Sosial, 2025)
Although waqf has long been recognised as a powerful Islamic socio-economic instrument, its utilisation in many Muslim communities remains largely consumptive and under-optimised. Existing studies tend to focus on traditional or partial models of productive waqf, offering limited insights into how waqf can be integrated with contemporary entrepreneurial practices to generate sustainable socio-economic impact. This study addresses this gap by examining Wakafpreneur, an innovative and integrated model that combines productive waqf with entrepreneurial frameworks to support da'wah initiatives and wider social transformation. Focusing on philanthropic institutions in Riau Province, Indonesia, this research aims to explore how the Wakafpreneur model is conceptualised, implemented, and experienced by its stakeholders. A qualitative case study approach was employed, drawing on in-depth interviews with waqf managers, participating entrepreneurs, and programme beneficiaries, as well as direct observations of Wakafpreneur business units. The findings demonstrate that Wakafpreneur significantly enhances the effectiveness of waqf management by transforming dormant waqf assets into sustainable business entities. This model not only generates independent financing streams for da'wah programmes but also promotes community economic empowerment through job creation, improved welfare outcomes, and the practical dissemination of Islamic values. The novelty of this study lies in its analysis of Wakafpreneur as a holistic and replicable model that positions waqf institutions as transformative agents within modern socio-economic ecosystems. The study recommends replicating the Wakafpreneur model in other regions as a strategic pathway to optimise waqf potential and strengthen the contribution of Islamic philanthropy to socio-economic development.